Respon Aplikasi Limbah Ampas Tahu dan POC Daun Gamal Terhadap Pertumbuhan Vegetatif dan Hasil Tanaman Lobak (Raphanus Sativus) - Purba, Eliakim; Yunidawati, Wiwik; Hasyim, Riyanti (Universitas Medan Area, 2024)
Radishes as root vegetables in the family Cruciferae, have limited growth in Indonesia. This is due to the lack of knowledge and use of radish, leading to low sales compared to other vegetables. However, radishes have significant development potential as a food ingredient because they can be eaten in almost all parts of the plant and have health benefits. One approach to increase soil and crop productivity is to use organic fertilizers, including tofu dregs waste and Gamal leaf POC. This study was conducted to evaluate the effect of giving tofu pulp waste and Gamal leaf POC on the growth and yield of radish plants. The research method involves the use of a Factorial Group Randomized Design (RAK) with two treatment factors. The results of the analysis showed that giving tofu pulp affected several growth parameters of radish plants while giving POC Gamal leaves did not have a significant effect. No significant interaction was found between the application of tofu pulp waste and Gamal leaf POC on the growth and yield of radish plants. In conclusion, giving tofu pulp waste can increase the growth of radish plants, while giving Gamal leaf POC did not have a significant effect in this study.